Dan Auta an African tale - Ortega y Gasset, José 1883-1955
"Kids 9 to 12 will laugh out loud while reading this adventurous graphic novel, which brings an African folk tale to life for a new audience. When Sarra's parents die, they leave her with an important warning: never let Dan Auta, her little brother, cry. But Dan Auta loves to make trouble. He hitches a ride on the back of a bird, pokes the eye of the king's son, and even pees on the king's head. Making sure he doesn't cry is much harder than Sarra thought! But Dan Auta's unbridled curiosity and determination may be exactly what everyone needs: a terrible monster called the Dodo is attacking the city... and Dan Auta is the only one with the courage to take him on. Dan Auta features: A delightful celebration of mischief and bravery A portrait of the extraordinary things kids are capable of when they follow their own paths Lively illustrations from renowned illustrator Piet Grobler Supplementary material that explains the folk tale's significance, including a note from an Eritrean translator."--
Keywords: Folk literature, African; Tales / Africa; Nigeria / Folklore; Littérature populaire africaine; Contes / Afrique; Tales; Nigeria; Africa / https://id.oclc.org/worldcat/entity/E39PBJkHrMyfHC67yqRTycbrv3; Children's stories / Comic books, strips, etc; Picture books; Folk tales; Graphic novels; picture books; folk tales; Juvenile works; Folklore; Fiction; Livres d'images; Contes; Bilderbuch; Comic